Synergistic Catalysis: Highly Enantioselective Acetyl Aza‐arene Addition to Enals. Issue 50 (10th August 2018) - Meazza, Marta; Sitinova, Gabriela; Poderi, Cecilia; Mancinelli, Michele; Zhang, Kaiheng; Mazzanti, Andrea; Torres, Ramon Rios
Abstract: A novel catalytic enantioselective methodology based on synergistic catalysis for the synthesis of chiral 2‐acyl pyridines and pyrazines is reported. The strategy involves the metal–Lewis acid activation of acetyl aza‐arenes and the secondary‐amine activation of enals. The proposed mechanism is supported by DFT calculations. Abstract : Synergistic synthesis : A novel catalytic enantioselective methodology based on synergistic catalysis for the synthesis of chiral 2‐acetyl pyridines and pyrazines is reported. The strategy involves (i) the metal–Lewis acid activation of acetyl aza‐arenes and (ii) the secondary‐amine activation of enals. DFT calculations support the proposed mechanism.